Understanding parents uncertainty sources and management strategies while caring for a child diagnosed with a hematologic cancer - Easton N. Wollney; Carma L. Bylund; Amanda L. Kastrinos; Gemme Campbell-Salome; Maria Sae-Hau; Elisa S. Weiss; Carla L. Fisher (Elsevier, 2023)
Rationale: Parents of a child or adolescent (CA) or young adult (YA) diagnosed with a hematologic cancer often face uncertainty. Managing uncertainty is critical to reduce the psychosocial burden of illness-related stressors. Objective: This study sought to identify: 1) sources of uncertainty among parents of a child diagnosed with a hematologic cancer, 2) strategies used by parents to manage uncertainty, and 3) clinicians' responses to parents' online information-seeking approach to managing uncertainty. Methods: Parents of CAs/YAs diagnosed with a hematologic cancer within the past 1-18 months and living in the U.S. participated in an in-depth, semi-structured phone interview (n = 20). Data were analyzed thematically. Results: Parents reported uncertainty about treatment (options, efficacy, and side effects or risks) and uncertainty about the future (recurrence, whether worry would subside, and how to approach the child's future). Parents managed uncertainty by seeking information online, talking to clinicians, and joining support groups. Clinicians' responses to online information-seeking were described as supportive and unsupportive. Conclusion: Parents described struggling with uncertainty across the cancer continuum (from primary treatment to survivorship). Parents' psychosocial health may benefit from individual and systems level interventions that help address and manage uncertainty, especially interventions focusing on parent caregiver-clinician communication.